Allocation concealment in randomised controlled trials: are we getting better?. (17th November 2016) - Clark, Laura; Fairhurst, Caroline; Torgerson, David J
Abstract : Laura Clark and colleagues assess the allocation concealment methods in a sample of randomised controlled trial publications